A flexible tool for a qualia-enriched FrameNet: the FrameNet Brasil WebTool. - Torrent, Tiago Timponi; Matos, Ely Edison da Silva; Costa, Alexandre Diniz da; Gamonal, Maucha Andrade; Peron-Corrêa, Simone; Paiva, Vanessa Maria Ramos Lopes (Language Resources & Evaluation, 2025)
In this paper we present a database management and annotation tool for running an enriched FrameNet database, the FrameNet Brasil WebTool. We demonstrate how the entity-based model of such a tool allows for the addition of two types of data-structure to FrameNet Brasil, both of which aimed at refining the granularity of the semantic representations: the frame element-to-frame and the ternary qualia relations. We report on three proof-of-concept applications of such an enriched database: a domain-specific structured lexicon, a recommendation system for tourists and a post-editing system for domain adaptation in machine translation.